Reservoir Characterization of Pila Spi Formation (Middle–Late Eocene) in Shaqlawa and Shekhan areas, Kurdistan Region, Northern Iraq - Edris M. Pirot; Ayad N. F. Edilbi (Tikrit Journal of Pure Science, 2022)
This study investigates reservoir quality for the Middle–Late Eocene Pila Spi Formation in Shaqlawa (Sarkand) and Gulley Keer (Shekhan) areas in Kurdistan Region of Iraq. Lithologically, the Pila Spi Formation in the studied sections is composed of limestone, dolomite, dolomitic limestone, chalky limestone, and marl. The thickness of the formation is about 102m and 200m in Sarkand and Gully Keer sections respectively. In order to evaluate the reservoir characterization of the studied formation, different techniques such as a microscopic study and core plug analysis were used. The Pila Spi Formation is characterized by several pore's types namely; vugs, moldics, channels, interparticles, fractures, boring, fenestral, and intragranulars. Several diagenetic processes were also recognized such as dolomitization, pressure solution, stylolization and dissolution. Based on the petrographic study, the lower part of the formation in Sarkand section has a porosity average of 8%, while it has an average of 21% and 17% in middle and upper parts. In Gulley Keer section, the porosity values of the formation are about 9%, 17, and 19%, in the lower, middle and upper part, respectively. The Scanning Electron Microscope (SEM) study shows almost the same porosity values, and the pore's sizes are between micropore to mesopore for the studied sections. Furthermore, the results of the core plugs analysis are roughly in agreement with optical assessments since the measured porosity values from Sarkand section are 8%, 18.5%, and 18% for lower, middle and upper parts, respectively. The porosity values of Gulley Keer section for lower, middle and upper parts of the studied section are 2.5%, 17.25%, and 22.5%, respectively. Consequently, the results revealed that the Pila Spi Formation has a good porosity except the lower part. In regards with permeability, the measured values of permeability displayed an avenge of 0.109md and 0.6698md for Sarkand and Gulley Keer respectively in which suggested fair to good permeability.